Land Use Change Analysis Using Remote Sensing and Markov Modeling in Fincha Watershed, Ethiopia - Ayana , Abdi Boru; Kositsakulchai, Ekasit (Agriculture and Natural Resources, 2012)
This study assessed land use and land cover change in the Fincha watershed located in Oromiya Regional State, Ethiopia, between 1985 and 2005 using the technologies of remote sensing and Markov modeling. The results indicated that agricultural land and water bodies have increased in area by 60,606 (53.59%) and 19,184 ha (93.10%), respectively. During this period, tremendous losses in forest, grazing land, swamp area and shrub lands were observed by as much as 36,225 (50.48%), 17,376 (31.23%), 19,948 (51.37%) and 6,240 ha (24.81%), respectively. During the study period, the land use and land cover change process showed no sign of being stable. The use of satellite remote sensing and Markov modeling was found to be beneficial in describing and analyzing the direction, rate and spatial pattern of land use and land cover change.